KESELAMATAN ALUR PELAYARAN MENGGGUNAKAN INFORMASI BATIMETRI MULTIBEAM ECHOSOUNDER (STUDI KASUS: PELABUHAN BELAWAN) - Febry Krisnanto; Yuwono Yuwono; Danar Guruh Pratomo (Kokoh, 2021)
The Belawan Harbor Shipping Line is the access used by ships that will dock and sail from the Belawan port. Belawan port itself is the largest port on the island of Sumatra, so many ships with large drafts enter the port. It takes a maintenance of the shipping lane by acoustic method so that the depth of the channel is maintained. The results showed that the depth of the Belawan port shipping lane was between -6 to -11 meters MSL. The depth plan that has been set by the port management is -8.5 meters MSL so that dredging of the channel is needed at several points. The results of the bathymetric data accuracy test based on the IHO S44 special order indicate that the survey still meets the tolerance. The tolerance threshold value given is 0.2617 meters and the standard deviation of the measurements in this study is 0.0480 meters. In addition, the value of the margin of error is 0.0480 meters.Keywords: Cruise line, IHO S44 Special Order, MSL, Ship draft